Importance of neuroimaging in neonatal congenital anophthalmia/microphthalmia: a case report - Andrés Armando Morilla Guzmán; Jesús Rabaza Pérez; Zonia América Blanco González (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Anophthalmia/microphthalmia is a congenital eye malformation that is characterized by the variable reduction of the volume of the ocular globe, which requires imaging studies for a more precise diagnosis. Objective: To demonstrate the importance of neuroimaging in the diagnosis and management of neonatal congenital bilateral anophthalmia/microphthalmia. Case Presentation:  We describe the case of a newborn with an initial clinical diagnosis of anophthalmia/microphthalmia in which, after carrying out neuroimaging studies, other malformations of the central nervous system were confirmed, allowing to guide the diagnosis towards a defined genetic syndrome. During the initial physical exam, hypertelorism, low set ears, palatine fissure, anterior anus, and absence of the ocular globes in both sides were verified. The magnetic resonance imaging showed signals of rudimentary crystalline located in an atypical area, and signals of incomplete optic nerve of the right side. Ocular globes were not observed. Multiple cyst-like bilateral images were also observed in orbital areas, displacing the rudimentary crystalline lens due to space limitations.   Discussion: This patient required neuroimaging studies to determine if she had an anophthalmia/microphthalmia and present a guide for the diagnosis of septo-optic dysplasia that organized the clinical thinking towards a possible Morsier Syndrome. In this case, a differential diagnosis with other causes associated to these ocular malformations was made. Conclusions: The imaging studies of the brain of the patients with anophthalmia/microphthalmia in the neonatal period allows to guide a precise and early diagnosis that favors an early multidisciplinary intervention.     Keywords: Newborn, eye malformations, congenital anophthalmia/microphthalmia, imaging studies, septo-optic dysplasia, nuclear magnetic resonance, Morsier Syndrome.